DSMC Approach for Rarefied Air Ionization during Spacecraft Reentry (Communications in Computational Physics, 2020)
The traditional DSMC method is extended to simulate three-dimensional(3D) rarefied ionization flows around spacecrafts during hypervelocity reentry. Theelectron mass amplification is utilized and the reaction rates involving electron aremodified correspondingly. A weighting factor scheme for trace species is proposed,and its impacts on collision mechanism, the realization of chemical reactions as well asthe calculations of macroscopic parameters are considered. The proposed DSMC algorithmis highly efficient in simulating weakly inhomogeneous flows, and its reliabilityis validated by the comparisons with aerodynamics force test of Shenzhou capsulemodel in low density wind tunnel, the electron number densities of RAM-C II andStardust in rarefied transitional flow regimes. The introduction of rare species weightingfactor scheme can significantly improves the smoothness of the number densitycontours of rare species, especially for that of electron in weak ionization case, whileit has negligible effect on the macroscopic flow parameters. The ionization characteristicsof the Chinese lunar capsule reentry process is analyzed for the first time at thealtitudes of 80km, 85km and 90km, and the predicted communication blackout altitudeagrees with the actual reentry flight data. The computation reveals that, for blunt bodyreentry with a speed larger than the second cosmic speed, the main ionization sourceis the direct collision ionization, and the electron number density is high enough tocause communication blackout in traditional rarefied flow regimes.